Reaksi Pasar Modal Terhadap Aksi Unjuk Rasa Bela Islam Jilid I, Jilid II & Jilid III (Studi Kasus: Perusahaan yang Tergabung Dalam Indeks LQ-45) - Agustian, Efandri (LPPM Universitas Adiwangsa Jambi, 2019)
The purpose of this study was to examine the information content of the Aksi Unjuk Rasa Bela Islam Jilid I, Jilid II dan Jilid III. Another objective are to examine the effect of the Aksi Unjuk Rasa Bela Islam Jilid I, Jilid II dan Jilid III on investor decision making in conducting transactions in the capital market which are seen from the abnormal return of shares and stock liquidity. The results of this study indicate: (1) That these three events of rallies did not contain information that made the capital market react. (2) That investor's reaction are to the events of Aksi Unjuk Rasa Bela Islam Jilid I, Jilid II dan Jilid III did not result in an overwhelming reaction to capital market. (3) Investor's reaction to events of Aksi Unjuk Rasa Bela Islam Jilid I, Jilid II dan Jilid III are relatively no different. (4) Whereas the investor's reaction to events of Aksi Unjuk Rasa Bela Islam Jilid I, Jilid II dan Jilid III are relatively no different.